Creating a Regional Business Development Map in Kazakhstan, 2014-2015 - Akhmetzhanov, Baurzhan (KDI School of Public Policy and Management, Global Delivery Initiative, 2020)
In 2014-15 the government of Kazakhstan embarked on a new undertaking: to create a regional business development map with the aim of providing comprehensive information on development opportunities for entrepreneurship and expanding support for entrepreneurs. The project faced numerous delivery challenges during implementation, including lack of available data and skilled human resources, as well opposition from government and businesses, which had to be carefully navigated. This case study examines the implementation process of the project, the approach of the Kazakhstani government to support businesses, and the results of these efforts. The regional business development map answers four main questions related to current business and potential entrepreneurship: 1. What is produced in the region? 2. Where is it economically feasible to do business? 3. Which business entities may become a driving force of development? and 4. What is the real business environment of the region? Thus, this project offers important insights to the Kazakhstani government in understanding what issues exist for entrepreneurs looking to create a company while identifying sectors of the economy where entrepreneurs need government support.
Keywords: To improve the ease of doing business; Skilled Human Resources; Opposition or lack of consensus; Data availability and baselines